New Real-Time PCR Assays for Detection of Inducible and Acquired Clarithromycin Resistance in the Mycobacterium abscessus Group - Shallom, Shamira J. (J Clin Microbiol, 2015)
Members of the Mycobacterium abscessus group (MAG) cause lung, soft tissue, and disseminated infections. The oral macrolides clarithromycin and azithromycin are commonly used for treatment. MAG can display clarithromycin resistance through the inducible erm(41) gene or via acquired mutations in the rrl (23S rRNA) gene. Strains harboring a truncation or a T28C substitution in erm(41) lose the inducible resistance trait. Phenotypic detection of clarithromycin resistance requires extended incubation (14 days), highlighting the need for faster methods to detect resistance. Two real-time PCR-based assays were developed to assess inducible and acquired clarithromycin resistance and tested on a total of 90 clinical and reference strains. A SYBR green assay was designed to distinguish between a full-length and truncated erm(41) gene by temperature shift in melting curve analysis. Single nucleotide polymorphism (SNP) allele discrimination assays were developed to distinguish T or C at position 28 of erm(41) and 23S rRNA rrl gene mutations at position 2058 and/or 2059. Truncated and full-size erm(41) genes were detected in 21/90 and 69/90 strains, respectively, with 64/69 displaying T at nucleotide position 28 and 5/69 containing C at that position. Fifteen isolates showed rrl mutations conferring clarithromycin resistance, including A2058G (11 isolates), A2058C (3 isolates), and A2059G (1 isolate). Targeted sequencing and phenotypic assessment of resistance concurred with molecular assay results. Interestingly, we also noted cooccurring strains harboring an active erm(41), inactive erm(41), and/or acquired mutational resistance, as well as slowly growing MAG strains and also strains displaying an inducible resistance phenotype within 5 days, long before the recommended 14-day extended incubation.